Herb-Induced Liver Injury by Cimicifuga racemosa and Thuja occidentalis Herbal Medications for Fertility. (18th January 2021) - Patel, Rohan; Alavi, Fareeha; Ortega, Susel; Matela, Ajsza
Abstract : Herb-induced liver injury (HILI) is often an underreported sequela for many herbal remedies due to the lack of safety measurements involving these supplements. Cimicifuga racemosa and Thuja occidentalis are two herbal medications commonly used by women for fertility purposes. Many herbal preparations of these two supplements do not specify the risks behind their individual usage. We present a case of a 40-year-old woman who developed acute liver injury after concomitant use of these two products assessed for causality using the updated RUCAM. Upon a detailed investigation, the patient did not have evidence of underlying liver disease or any other risk factors to explain her presentation. After discontinuation of both herbal supplements, the patient had complete resolution of her symptoms and a significant improvement of transaminitis. This report highlights the importance of potential risk of hepatotoxicity induced by concomitant use of Cimicifuga racemosa and Thuja occidentalis .